New encyclopedia of Africa Volume 3 - Middleton, John, 1921-2009.; Miller, Joseph Calder (Detroit : Thomson/Gale, 2008)
This substantial expansion and reworking of the classic Encyclopedia of Africa South of the Sahara (1997) covers the entire continent, from the Europe-facing shores of the Mediterranean to the commercial bustle of Cape Town. The set addresses the entire history of African cultures from the pharaohs and the ancient civilizations of the south through the colonial era to the emergence of 53 independent countries, some of them, like Nigeria, newly emergent in world commerce and others deep in conflict (Sudan, Liberia, Congo). The NEA treats todays African peoples not as the obscure 2other3 of a 2Dark Continent3 but as actors on a world stage where issues of global development, the AIDS crisis, and international terrorism play out across a map where indigenous cultures continue to function beneath an imperfect European overlay of 2national states. 3 Anthropology, geography, history, and cultural studies by an international team of more than 600 distinguished Africanists (including over 150 from Africa and the African Diaspora) show us Africaas seen by Africans themselves. Features hundreds of photographs, including five color essays, plus maps, thematic outline, chronology, and appendix of ethnic and identity groups. - Publisher.
v. 1. Abd al-Qadir-Cummings-John -- v. 2. Dakar-Hydrology -- v. 3. Ibadan-Mzilikazi -- v. 4. Nairobi-Symbols -- v. 5. Taboo and Sin-Zubayr, Index.
"Successor to the Encyclopedia of Africa South of the Sahara that was conceived in 1991 by the late Charles E. Smith of Simon & Schuster and was eventually published by Charles Scribner's Sons of New York in 1997"--Page xxix.
Includes bibliographical references and index.
Keywords: Africa -- Encyclopedias; Afrique -- Encyclopédies; Africa; Africa; Encyclopedias; Geography of Africa; Encyclopedias; Reference works; Encyclopedias; Reference works